(untitled) (Eurasian Journal of Ecology, 2016)
The ecological characteristics of the NE Caspian Sea and assessment of the planktonic community status were provided. Abiotic and biotic factors that determine formation offavorable conditions in the NE Caspian Sea as well as peculiarities of distribution and habitats of main planktonic organisms were analyzed. The impact of temperature and salt regime on development ofphytoplankton and zooplankton was assessed.